2021
DOI: 10.3390/nano11082105
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide and Reduced Graphene Oxide Nanoflakes Coated with Glycol Chitosan, Propylene Glycol Alginate, and Polydopamine: Characterization and Cytotoxicity in Human Chondrocytes

Abstract: Recently, graphene and its derivatives have been extensively investigated for their interesting properties in many biomedical fields, including tissue engineering and regenerative medicine. Nonetheless, graphene oxide (GO) and reduced GO (rGO) are still under investigation for improving their dispersibility in aqueous solutions and their safety in different cell types. This work explores the interaction of GO and rGO with different polymeric dispersants, such as glycol chitosan (GC), propylene glycol alginate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…Graphene‐based nanomaterials coated with biocompatible polymers such as chitosan and dextran have lower hemolytic activity than unreformed graphene. A recent study also showed that the dispersion of GO (100 μg/ml) and rGO (100 μg/ml) in polymeric surfactants, including glycol chitosan (GC), propylene glycol alginate (PGA), and polydopamine (PDA), improved the stability of the suspensions 52 . It showed that cytotoxic effects induced by coated materials, especially those coated with PGA, on human chondrocytes are lower than those of the control.…”
Section: Biocompatibility Of Graphene‐based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene‐based nanomaterials coated with biocompatible polymers such as chitosan and dextran have lower hemolytic activity than unreformed graphene. A recent study also showed that the dispersion of GO (100 μg/ml) and rGO (100 μg/ml) in polymeric surfactants, including glycol chitosan (GC), propylene glycol alginate (PGA), and polydopamine (PDA), improved the stability of the suspensions 52 . It showed that cytotoxic effects induced by coated materials, especially those coated with PGA, on human chondrocytes are lower than those of the control.…”
Section: Biocompatibility Of Graphene‐based Nanomaterialsmentioning
confidence: 99%
“…A recent study also showed that the dispersion of GO (100 μg/ml) and rGO (100 μg/ml) in polymeric surfactants, including glycol chitosan (GC), propylene glycol alginate (PGA), and polydopamine (PDA), improved the stability of the suspensions. 52 It showed that cytotoxic effects induced by coated materials, especially those coated with PGA, on human chondrocytes are lower than those of the control. Most studies showed that the toxicity of graphene and GO is associated with its interaction with the cell membrane, which physically harms the lipid membrane.…”
Section: Surface Modifications Of Graphene-based Nanomaterials For In...mentioning
confidence: 99%
“…No insights are reported in the state of the art so far regarding the use of PGA for BTNP coating. In the literature, PGA has been proposed for stabilizing graphene oxide nanoflakes, 55 demonstrating high biocompatibility and the ability to keep these nanomaterials well dispersed in aqueous media. However, the dimensions of these flakes (lateral dimension: ∼10 µm, thickness: ∼1.5 nm) were not comparable with the ones of BTNPs used in this study.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…A repeated sterilization test was performed as per ISO 17665-1 standard for assessing the effect of sterilization temperature on the adhesion property of the black oxide coating [29]. In the conventional method, the temperature of the steam varies from 121-134 • C for a period of 15−21 min to ensure adequate sterilization.…”
Section: Repeated Sterilization and Morphology Studiesmentioning
confidence: 99%